Stress Concentration Factor in vessels with circular crosshole: Continuous parameters analysis - Gimeno, Jaime; Venegas Pereira, Oscar Hernando; Urbano Tole, Javier Andrés (ElSevier, 2022)
In this paper, a parametric study of the Stress Concentration Factor (SCF) has been carried out in cylindrical pressure vessels with circular holes. A three-dimensional finite element analysis has been carried out performing a variation of dimensionless parameters (thickness ratio, size ratio and aspect ratio) exploring a wider range than other investigations. It is observed that the maximum value of the SCF increases as the hole size ratio and the aspect ratio increase, although the location of the maximum SCF is located from the internal area of the vessel to the external part depending on the geometric configuration, defining thus three differentiated zones. Additionally, in the final part of the document, a fit model is defined to determine the value of the maximum SCF for different continuous values of the defined dimensionless parameters. This model allows to quickly calculate or locate from a contour map the maximum value of SCF for a specific geometry of pressure vessel.

En este trabajo se ha realizado un estudio paramétrico del factor de concentración de tensiones (SCF) en recipientes a presión cilíndricos con orificios circulares. Se ha llevado a cabo un análisis tridimensional por elementos finitos realizando una variación de los parámetros adimensionales (relación de espesores, relación de tamaños y relación de aspectos) explorando un rango más amplio que otras investigaciones. Se observa que el valor máximo del SCF aumenta a medida que se incrementa la relación de tamaño de los agujeros y la relación de aspecto, aunque la localización del SCF máximo se localiza desde la zona interna del recipiente hasta la parte externa dependiendo de la configuración geométrica, definiendo así tres zonas diferenciadas. Adicionalmente, en la parte final del documento, se define un modelo de ajuste para determinar el valor del SCF máximo para diferentes valores continuos de los parámetros adimensionales definidos. Este modelo permite calcular o localizar rápidamente a partir de un mapa de contornos el valor máximo de SCF para una geometría específica de recipiente a presión.
Keywords: Stress concentration factor; Thick pressure vessels; Crossholes; High-pressure vessels; Finite element method